From microsermons to memes. On the small homiletics forms by Rev. Eugeniusz Burzyk - Bizior, Renata (Papers in Linguistics, 2019)
This paper takes up the issues of creating new preaching forms: triptych sermons (micro-sermons) and memes with sermons and how they function in the perspective of linguistic genology. Characteristics of species forms which are transformations of other genre patterns are embedded in the contemporary cultural context. This study presents new forms of the genre against several contextual considerations: cultural and communications transformations determined by the development of digital technologies and the assumptions of the new evangelization program implemented by the Church combined with the attitude of open Catholicism presented by their author, Rev. Eugeniusz Burzyk. The article discusses the usefulness of the model of short triptych sermons and the adaptation of internet memes for the needs of the new evangelization. The analysed preaching texts are presented as forms (specimens) breaking with the canonical genre pattern, crossing the boundaries of the genre, hybridism and taking up polemics with the genre tradition. The study characterizes specific features of both related forms of the genre: sermons (microsermons) and memes with sermons.